Overexpression of NtDOG1L-T Improves Heat Stress Tolerance by Modulation of Antioxidant Capability and Defense-, Heat-, and ABA-Related Gene Expression in Tobacco - Dai, Xiaoyan; Wang, Yingfeng; Chen, Yanchun; Li, Hongchen; Xu, Shixiao; Yang, Tiezhao; Zhang, Xiaoquan; Su, Xinhong; Xia, Zongliang (Frontiers in Plant Science, 2020)
Drought and heat stresses are two major environmental stress factors that severely threaten crop growth and productivity. Plant DELAY OF GERMINATION 1-like (DOG1L) family genes play important roles in various developmental processes and stress responses. In our previous study, a tobacco DOG1L gene (NtDOG1L-T) was found to regulate seedling growth and drought response. Unfortunately, the role of DOG1L genes in heat stress response is yet to be studied. Here, we present data supporting the role of DOG1L genes in heat stress and possible underlying molecular mechanisms. Transcript levels of NtDOG1L-T were rapidly induced by heat or ABA treatment. Furthermore, NtDOG1L-T promoter activity was markedly activated by ABA or heat stress, as revealed by histochemical staining in transgenic tobacco seedlings. Over-expression of NtDOG1L-T in transgenic lines improved heat stress tolerance. The NtDOG1L-T-transgenic plants exhibited lower levels of reactive oxygen species and lipid peroxidation, but higher antioxidant enzyme activities in response to heat stress. Furthermore, transcript abundance of some defense-, heat-, and ABA-responsive marker genes was significantly up-regulated, as shown by reverse transcription quantitative PCR in these transgenic plants. In conclusion, NtDOG1L-T positively regulates heat stress tolerance possibly by modulation of antioxidant capability and defense-, heat-, and ABA-related gene expression in tobacco. This study may provide valuable resource for the potential exploitation of DOG1Ls in genetic improvement of heat stress tolerance in crops.